Development of BRCA1 DNA Sequence Profile of Early Diagnosis of Breast Cancer - Nurdin, D. S.; Isa, M. N.; Ismail, R. C.; Ahmad, M. I. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
Early disease detection using gene expression has been widely discussed for many diseases including breast cancer, mainly by the detection of mutations in DNA sequence. However, aligning long BRCA1 gene is rather time-consuming for early detection. The implementation of systolic architecture in FPGA which an accelerator could solve the computation time drawback. Despite that, all of the BRCA1 DNA NTs are unable to be fitted in the FPGA. Thus, the BRCA1 gene needs to be truncated for real-time detection without affecting its accuracy. The exon 11 of BRCA1 is selected as test sequence where it is truncated for 80%, 60%, 40% and 20% from 3 different locations i.e. front, middle and end. Based on the results, exon 11 which is truncated for 60% from the middle part is selected as the developed profile for early detection of breast cancer using BRCA1 gene.